2014
DOI: 10.1038/pr.2014.151
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-31 promotes helper T cell type-2 inflammation in children with allergic rhinitis

Abstract: Background: Interleukin-31 (IL-31) is a recently described cytokine that is involved in helper T cell type-2 (Th2)-mediated diseases. However, its regulatory effect in the pathogenesis of children allergic rhinitis (AR) needs to be further characterized. This study sought to evaluate the expression and role of IL-31 in children with AR. Methods: Sixty children with AR and 20 normal controls were included. IL-31 and Th2 cytokines production in tissue, serum, and nasal lavage was examined by immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…IL31 was previously shown to regulate cytokine production by airway epithelial cells 53 , and to be promoted by IL4, driving Th2 type inflammation 54 . Previous studies also indicated increased expression of IL31 in allergic asthma and allergic rhinitis 36,55 . As such, the regulation of IL31 may in part explain the Th2 skewing we observed in the WNT5A transgenic mouse and support a potential role for WNT5A in Th2 type inflammation and allergic asthma.…”
Section: Discussionmentioning
confidence: 81%
“…IL31 was previously shown to regulate cytokine production by airway epithelial cells 53 , and to be promoted by IL4, driving Th2 type inflammation 54 . Previous studies also indicated increased expression of IL31 in allergic asthma and allergic rhinitis 36,55 . As such, the regulation of IL31 may in part explain the Th2 skewing we observed in the WNT5A transgenic mouse and support a potential role for WNT5A in Th2 type inflammation and allergic asthma.…”
Section: Discussionmentioning
confidence: 81%
“…Increased IL-31 protein and mRNA levels have been shown both in patients with allergic asthma and those with rhinitis (Table I). [72][73][74] IL-31 single nucleotide polymorphisms were significantly correlated with serum IgE levels in asthmatic patients. 75 Among patients with asthma/rhinitis with positive specific IgE levels, patients with dust mite and mugwort allergy had higher IL-31 levels.…”
Section: Il-31 In Patients With Nondermatologic Diseasesmentioning
confidence: 94%
“…72 Increased local secretion of T H 2 cytokines and mucin production have been reported in patients with allergic rhinitis after induction with IL-31. 74 Therefore the IL-31 pathway might be a potential target in the treatment of allergic asthma and rhinitis.…”
Section: Il-31 In Patients With Nondermatologic Diseasesmentioning
confidence: 99%
“…However, recent studies imply that IL-31 might also be involved in allergic asthma and rhinitis [150][151][152], in inflammatory bowel disease [144] and malignancies of hematopoietic and lymphoid tissues [119,134,153]. Recent reviews summarize these findings in detail [123,124,154].…”
Section: Animal Models Investigating Il-31 Physiology and Recent Findmentioning
confidence: 99%